Percepção de gestores de escolas públicas municipais de Cascavel/ PR, no uso de dados das avaliações em larga escala em suas práticas educacionais - Machado, Celso (2022)
The school manager is a decisive professional in the educational process and holds under his responsibility activities related to large-scale evaluations, in a constant search for the improvement of educational quality. However, there are weaknesses in relation to the real perception of this professional on how to use the data resulting from the evaluations to guide his directive and pedagogical actions in the teaching unit. The objective of this study is to analyze how managers perceive the large-scale evaluations and if they use their results to guide educational actions. It aims to understand if and how the managerial intervention occurs, which strategies are mobilized to promote reflection on how the results can be used by the school collective. In this sense, as a research tool, we used literature review and field research, including the application of online questionnaires, Google® Forms to collect data from managers of public municipal schools in Cascavel, PR. The study is characterized as qualitative and descriptive, and was developed with the Graduate Program in Education of the State University of Western Paraná, in the research line on Education, Social Policies and State. The analysis, supported by authors, revealed that the state has always carried out actions focused on evaluations, encouraging competition among schools and teachers that leads to a ranking of education, as well as accountability policies. The managerial action in the context of large-scale evaluation, in a minimal action, points to the fact of the need to improve the process of using the results for the entire school community, so that this information can be used in the pedagogical planning of schools, aiming for advances in the development of their work and in student learning. Thus, the data collected revealed the need for advances in the comprehensive understanding of the correct use of the results of large-scale assessments by the school manager.